Avitus of Vienne : letters and selected prose - Avitus, Alcimus Ecdicius, asi 455-518 (Translated texts for historians ;, 2002)
This copious selection from the letters of Avitus, who was Bishop of Vienne from c.494 to c.518, gives scholars and students access to a very important source for the history of the Burgundian kingdom and the late antique world. There is an excellent, and very full, introduction, and each letter is accompanied by notes which enable the reader to situate it in the intellectual, polemic, and political currents of the sixth century.